Legal Profession Code of Ethics as Justice Enforcement for Professional Judges - Achmad Ghani (CIC Lembaga Riset dan Konsultan Sosial, 2020)
Ethics of living side by side and being tied to each other in the life of many people. Ethics has control over the creation of a mindset and treatment of the values ​​of goodness that must be done and evil that must be avoided. The concept of ethical practice affects every professional in all fields, including the legal profession. The bearer of the legal profession is a person who has expertise and ability in the field of law. The knowledge that is owned is independently able to meet the needs of people who seek service and justice according to their expertise. Judges in their profession are deciding cases that are present at court. Of course, the fulfillment of the right to justice before the law is the ultimate goal of a profession that he carries. In deciding a case, a judge must be based on his knowledge, moral independence, and also the code of ethics for the judge's profession that is inherent in him in order to create a just decision based on divinity.